Caracterización bibliográfica de Escherichia coli asociada a muerte de terneros en bovinos lecheros. - De La Gala Moreira, Tamar Melissa (2022)
Bovine diarrhea is a limiting factor for livestock development in Ecuador and worldwide. The most important infectious agent of colibacillosis with the greatest influence in cattle ranches is the bacterium Echerichia coli, Echerichia coli is a large negative bacterium that was described for the first time in 1885 by the German bacteriologist Theodore von Escherich. It is a bacillus that reacts negatively to Gram stain (gram-negative), is facultatively anaerobic, motile by peritrichous flagella and is a microorganism that ferments glucose and lactose, is catalase positive, oxidase negative and reduces nitrates to nitrites. This described agent causes in the calf different affectations such as dehydration, alterations in its gastrointestinal tissues, weight loss, delays in puberty and reproduction, and in its development stage. If it is not treated in time by taking a protocol, the bacteria will cause the death of the calf, all due to the toxins secreted by the bacteria in the intestinal flora of the bovine, therefore, the losses can be very high for the cattle community and low calf production in Ecuador. This research is able to determine the antigenic infection process and the biochemical structure of Escherichia coli bacteria, the pathological effect and the preventive measures for its propagation based on articles and studies carried out. Taking into account the importance of the bacterium that affects other animal species including humans, it is highly zoonotic and the concern for the causes that it presents in the host and its consequence will be certain diseases, therefore, for the control of the bacterium will have to be considered by each country.